2004
DOI: 10.1001/archinte.164.9.982
|View full text |Cite
|
Sign up to set email alerts
|

Admission Blood Glucose Level as Risk Indicator of Death After Myocardial Infarction in Patients With and Without Diabetes Mellitus

Abstract: Admission blood glucose level after AMI is an independent predictor of long-term mortality in patients with and without known diabetes. Subjects with unknown diabetes and admission glucose levels of 200 mg/dL (11.1 mmol/L) or more after AMI have mortality rates comparable to those of subjects with established diabetes. Admission blood glucose level may serve to identify subjects at high long-term mortality risk, in particular among those with unknown diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
204
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(222 citation statements)
references
References 38 publications
11
204
0
7
Order By: Relevance
“…Also, despite the lower blood This is the first study to assess the association of glycemic state upon hospital admission with the myocardium area at risk and myocardial salvage in a large cohort of patients with STEMI. Our data suggest that the excessive myocardial damage (5-8) and adverse prognosis (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) reported in patients with hyperglycemia are the results of a larger myocardial area at risk, and not of a smaller myocardial salvage. Similarly, since there was no association between hyperglycemia and infarct size when adjusting for the area at risk, the current study demonstrates that the association between hyperglycemia and infarct size is dependent on the size of the area at risk, and hyperglycemic patients can therefore be considered to be at higher risk per se.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Also, despite the lower blood This is the first study to assess the association of glycemic state upon hospital admission with the myocardium area at risk and myocardial salvage in a large cohort of patients with STEMI. Our data suggest that the excessive myocardial damage (5-8) and adverse prognosis (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) reported in patients with hyperglycemia are the results of a larger myocardial area at risk, and not of a smaller myocardial salvage. Similarly, since there was no association between hyperglycemia and infarct size when adjusting for the area at risk, the current study demonstrates that the association between hyperglycemia and infarct size is dependent on the size of the area at risk, and hyperglycemic patients can therefore be considered to be at higher risk per se.…”
Section: Discussionmentioning
confidence: 68%
“…The mechanisms behind reperfusion injury have not been fully elucidated, but hyperglycemia, which is observed in approximately half of patients with STEMI upon hospital admission (3), may be unfavorable during reperfusion and has been linked to the subsequent injury (4). Previous studies have demonstrated larger infarct size (5)(6)(7)(8) and poorer prognosis in patients with hyperglycemia upon hospital admission compared with patients without hyperglycemia, both in patients with and without diabetes mellitus (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Until now, the impact of hyperglycemia on myocardial salvage has been evaluated in only a limited number of patients (21), and no data exist regarding the relationship between hyperglycemia and area at risk.…”
mentioning
confidence: 99%
“…Many prior studies have observed that the nature of the relationship between initial glucose levels and short-term mortality differs between patients with and without diabetes. 2,15,21,29,30,32 The risk of mortality rises gradually once glucose levels exceed ~110-120 mg/dL (6.1-6.6 mmol/L) in patients without diabetes, whereas in patients with established diabetes the risk does not increase substantially until glucose levels exceed ~200 mg/dL (11.0 mmol/L). 2,29 Thus, different definitions of hyperglycaemia may be appropriate according to whether established diabetes is present.…”
Section: Hyperglycaemia Definitionmentioning
confidence: 99%
“…Indeed, admission hyperglycemia has been linked to poor clinical outcomes in hospitalized patients for a variety of conditions, particularly for myocardial infarction, stroke, and critical illness. [12][13][14][15] In this study, we evaluated recognition, communication, and management of ED glucose values above a relatively conservative threshold of 140 mg/dL, occurring in 21% of ED glucose results. Diabetes screening thresholds for casual glucose values as low as 120 mg/dL, 9 and intensive glycemic control in critically ill patients to a target as low as 110 mg/dL have been suggested.…”
Section: Discussionmentioning
confidence: 99%